2007
DOI: 10.1016/j.immuni.2007.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of CD4 and CD8 Coreceptors Permits Generation of αβT Cells that Recognize Antigens Independently of the MHC

Abstract: The thymus generates major histocompatibility complex (MHC)-restricted alphabetaT cells that only recognize antigenic ligands in association with MHC or MHC-like molecules. We hypothesized that MHC specificity might be imposed on a broader alphabetaTCR repertoire during thymic selection by CD4 and CD8 coreceptors that bind and effectively sequester the tyrosine kinase Lck, thereby preventing T cell receptor (TCR) signaling by non-MHC ligands that do not engage either coreceptor. This hypothesis predicts that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
211
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(228 citation statements)
references
References 41 publications
15
211
1
1
Order By: Relevance
“…However, associated biophysical, thermodynamic, and mutational studies have also shown that the relative energetic contributions from the CDR loops can vary between the various TCR-pMHC systems (10,11). Accordingly, it is also considered that extrinsic factors, such as the CD8 coreceptor, play a principal role in MHC restriction, which is consistent with recent observations from CD8 − CD4 − mice (12,13). Nevertheless, in the absence of the CD8 or CD4 coreceptor, a rough docking mode between the TCR-pMHC is preserved, so that for pMHC-I, the Vα and Vβ domains are positioned over the MHC α2-and α1-helices, respectively (2), suggesting some hidden logic in TCR-pMHC-I engagement.…”
supporting
confidence: 83%
“…However, associated biophysical, thermodynamic, and mutational studies have also shown that the relative energetic contributions from the CDR loops can vary between the various TCR-pMHC systems (10,11). Accordingly, it is also considered that extrinsic factors, such as the CD8 coreceptor, play a principal role in MHC restriction, which is consistent with recent observations from CD8 − CD4 − mice (12,13). Nevertheless, in the absence of the CD8 or CD4 coreceptor, a rough docking mode between the TCR-pMHC is preserved, so that for pMHC-I, the Vα and Vβ domains are positioned over the MHC α2-and α1-helices, respectively (2), suggesting some hidden logic in TCR-pMHC-I engagement.…”
supporting
confidence: 83%
“…Most dramatically, one laboratory constructed a mouse lacking MHCI, MHCII, CD4, and CD8 and introduced mutations to uncouple essential downstream TCR-signaling molecules from essential interactions (47)(48)(49). The mice developed a peripheral T-cell repertoire that contains T cells reactive to the surface protein CD155.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, V␥9V␦2 ϩ T cells lack the coreceptors CD8 and CD4, which restrict antigen recognition in ␣␤ T cells to peptides that are presented in conjunction with MHC I and MHC II molecules, respectively. As a consequence, this allows selectivity for nonpeptide antigens without impairing signal strength (24) and, at the same time, releases the constraint for the need of conventional APCs for induction of V␥9V␦2 ϩ T cell responses. A second distinguishing feature of V␥9V␦2 ϩ T cells is their broad, polyclonal activation by a single class of nonpeptide ligands derived from microbes or stressed tissue cells with alternative or aberrant isoprenoid metabolism (7,8).…”
Section: Discussionmentioning
confidence: 99%